2002
DOI: 10.1300/j096v08n02_09
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Dust and Ammonia on the Occupational Health Effects of Poultry Production Workers

Abstract: Control of both dust and ammonia in livestock facilities is extremely important. Lack of control of both these contaminants will increase the risk of respiratory dysfunction to all exposed to this environment, including workers and veterinarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 43 publications
(49 reference statements)
0
48
0
1
Order By: Relevance
“…[1] When discharged from exhaust fans of poultry and livestock housing these hazardous emissions may have environmental impacts not only to the ecosystem near the source but also at distances from the source depending on fan speed and climatic conditions. [1−3] Respiratory dysfunction among farm workers from dust and ammonia exposure have been documented by Donham et al [4] Odors adhering to the farm emissions have also been an increasing nuisance to neighbors. [5] In the atmosphere, aerosol particulates formed by NH 3 with other gases are deposited and may cause further acidification of the land and eutrophication of surface water.…”
Section: Introductionmentioning
confidence: 99%
“…[1] When discharged from exhaust fans of poultry and livestock housing these hazardous emissions may have environmental impacts not only to the ecosystem near the source but also at distances from the source depending on fan speed and climatic conditions. [1−3] Respiratory dysfunction among farm workers from dust and ammonia exposure have been documented by Donham et al [4] Odors adhering to the farm emissions have also been an increasing nuisance to neighbors. [5] In the atmosphere, aerosol particulates formed by NH 3 with other gases are deposited and may cause further acidification of the land and eutrophication of surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, poultry workers completed pulmonary function tests before and after each shift and the relationship of total dust and ammonia exposures were examined by correlation, logistic modeling, and synergy index calculations. Results of this study concluded that synergistic effects between ammonia and aerosolized dust concentrations explained up to 43-63% of the pulmonary function decline over the work shift (Donham et al, 2002 There are no recommended exposure limits or standards provided by these agencies for endotoxin, pathogens or organic dust. Although recommendations can be found in the literature, these are not enforceable and are driven by research, as opposed to enforceable PELs.…”
Section: Health Effects From Contaminantsmentioning
confidence: 86%
“…Donham et al (2002) reported synergistic effects between dust and ammonia exposures associated with decreases in pulmonary function among workers in poultry production. Specifically, poultry workers completed pulmonary function tests before and after each shift and the relationship of total dust and ammonia exposures were examined by correlation, logistic modeling, and synergy index calculations.…”
Section: Health Effects From Contaminantsmentioning
confidence: 99%
“…Grain dusts contribute heavily to agricultural dust composition among swine, dairy and poultry farms (Donham et al, 2002;Lee et al, 2006). It is well established that occupational exposure to agricultural dusts is a risk factor for respiratory dysfunction in swine and poultry facility workers chronically exposed to dust consisting of feed particles, bacterial endotoxin, gases and other components (O'Shaughnessy et al, 2010;Viegas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosols, volatile compounds, gases and inorganic compounds including alcohols, aromatics and nitrogenrelated contribute to animal production dust complexity (Plummer et al, 2009;Chmielowiec-Korzeniowska, 2009;Hamon et al, 2012). Simultaneous exposure to poultry production dust particulates and ammonia resulted in a synergistic decline in pulmonary function in workers (Donham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%